Effects of Oceanic Mesoscale and Submesoscale Frontal Processes on the Vertical Transport of Phytoplankton. Issue 8 (23rd August 2019) - Ruiz, Simón; Claret, Mariona; Pascual, Ananda; Olita, Antonio; Troupin, Charles; Capet, Arthur; Tovar‐Sánchez, Antonio; Allen, John; Poulain, Pierre‐Marie; Tintoré, Joaquín; Mahadevan, Amala
Abstract: Oceanic fronts are dynamically active regions of the global ocean that support upwelling and downwelling with significant implications for phytoplankton production and export. However (on time scales  ≳  the inertial time scale), the vertical velocity is 10 3 –10 4 times weaker than the horizontal velocity and is difficult to observe directly. Using intensive field observations in conjunction with a process study ocean model, we examine vertical motion and its effect on phytoplankton fluxes at multiple spatial horizontal scales in an oligotrophic region in the Western Mediterranean Sea. The mesoscale ageostrophic vertical velocity (∼10 m/day) inferred from our observations shapes the large‐scale phytoplankton distribution but does not explain the narrow (1–10 km wide) features of high chlorophyll content extending 40–60 m downward from the deep chlorophyll maximum. Using modeling, we show that downwelling submesoscale features concentrate 80% of the downward vertical flux of phytoplankton within just 15% of the horizontal area. These submesoscale spatial structures serve as conduits between the surface mixed layer and pycnocline and can contribute to exporting carbon from the sunlit surface layers to the ocean interior. Key Points: High‐resolution observations and numerical simulations of mesoscale and submesoscale features at an intense oceanic front Vertical velocities associated with submesoscale features are significantly higher than on the mesoscale Downwelling submesoscale features concentrate 80% of downward flux of phytoplankton within 15% of the surface area